Towards Green Building ( Fine Arts Building ) - Ayah Hassan; Ghadeer Otear; Saja Sweidan (My University, 2011)
Case study: Fine Arts Building( at An Najah national University)The Project  Idea Modify Certain aspects  to make the Building  more  environmentally friendly (green).